2021
DOI: 10.1136/bmjgh-2021-005202
|View full text |Cite
|
Sign up to set email alerts
|

Ethics-driven policy framework for implementation of movement restrictions in pandemics

Abstract: In the ongoing COVID-19 pandemic, countries across the globe undertook several stringent movement restrictions to prevent the virus spread. In April 2020, around 3.9 billion people in 90 countries were contained in their homes. Discourse on the ethical questions raised by such restrictions while historically rich is absent when it comes to pragmatic policy considerations by the decision-makers. Drawing from the existing literature, we present a unified ethical principles–pragmatic considerations–policy indicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…We further observed that there was excess focus on the anticipated efficacy of the interventions rather than to scale up the healthcare resources, and thus preparedness for the impact of the pandemic was lost. This was more of a speculated efficacy, and thus, very short-sighted policy implications with little consideration of societal implications and ethical concerns of the lockdown interventions 31 .…”
Section: Discussionmentioning
confidence: 99%
“…We further observed that there was excess focus on the anticipated efficacy of the interventions rather than to scale up the healthcare resources, and thus preparedness for the impact of the pandemic was lost. This was more of a speculated efficacy, and thus, very short-sighted policy implications with little consideration of societal implications and ethical concerns of the lockdown interventions 31 .…”
Section: Discussionmentioning
confidence: 99%
“…According to an Indian policy framework by Zadey, Dharmadhikari & Mukuntharaj (2021), where the extent of harm that a potential pathogen poses is unknown, decision-making and guidelines regarding restrictions of human rights must be clearly communicated, equitable and reciprocal. Such decision-making must uphold the use of least restrictive means and, as more information unfolds, decisions must be guided by the principles of preventing harm, justifiability and proportionality [45]. Other authors in Western cultures focused on such restrictions being justified in light of the risk of negative outcomes to others, particularly in the absence of a vaccine [12,19,46].…”
Section: Theme 5: Procedural Justice Of Lockdownmentioning
confidence: 99%
“…Finally, there is some limited debate regarding the ethicality and fairness of lockdown within the literature, particularly in those with fewer economic means and less reliable access to food, water and sanitation [47]. Some authors argued that decision-making regarding lockdown must adopt the least restrictive means possible until clear information on a pathogen and the risks it poses emerge, whilst others argue that lockdown is justified where there is substantial risk of loss of life [12,19,45,46].…”
Section: Summary Of Findingsmentioning
confidence: 99%